Optimization techniques for petroleum engineering: A brief review. (3rd September 2021) - Kumar, Anuj; Vohra, Mridul; Pant, Sangeeta; Singh, Sanjeev Kumar
ABSTRACT: Optimization in the production of oil comprises various processes to measure, analyze, model, prioritize, and implementation to enhance productivity of a field, reservoir, well, or surface. It is a practice to ensure recovery of developed reserves while maximizing returns. With the advancement of technologies associated with the field of petroleum engineering, there has always been an advent of an optimization technique. Albeit not abruptly but still with considerable consistency, conventional as well as nature inspired optimization techniques extend their roots in almost all complex problems of the world including petroleum engineering. In this article, we have reviewed the extensive use of optimization-based procedures and approaches in petroleum engineering that are being used to expand, develop, and generate petroleum fields with the appropriate designs and operations; reservoir development, planning and management.